Pembelajaran Menulis Berbasis Karakter Character-Based Writing Learning - Miftahul Husna; Fadhilah Uswah; Lismayani Siregar (Universitas Dehasen Bengkulu, 2022)
This study aims to determine character-based writing learning. Character-based writing learning uses a whole language approach, especially combining reading and writing. The character-based writing learning consists of five stages. Namely: pre-writing stage, drafting stage, editing stage, revising stage, and publication stage.